Aging triggers a repressive chromatin state at Bdnf promoters in hippocampal neurons - Palomer, Ernest (2016)
Cognitive capacities decline with age, an event accompanied by the altered transcription of synaptic plasticity genes. Here, we show that the transcriptional induction of Bdnf by a mnemonic stimulus is impaired in aged hippocampal neurons. Mechanistically, this defect is due to reduced NMDA receptor (NMDAR)-mediated activation of CaMKII. Decreased NMDAR signaling prevents changes associated with activation at specific Bdnf promoters, including displacement of histone deacetylase 4, recruitment of the histone acetyltransferase CBP, increased H3K27 acetylation, and reduced H3K27 trimethylation. The decrease in NMDA-CaMKII signaling arises from constitutive reduction of synaptic cholesterol that occurs with normal aging. Increasing the levels of neuronal cholesterol in aged neurons in vitro, ex vivo, and in vivo restored NMDA-induced Bdnf expression and chromatin remodeling. Furthermore, pharmacological prevention of age-associated cholesterol reduction rescued signaling and cognitive deficits of aged mice. Thus, reducing hippocampal cholesterol loss may represent a therapeutic approach to reverse cognitive decline during aging.